2021
DOI: 10.21203/rs.3.rs-154681/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk Factors for Bacterial Infections in Patients With Moderate to Severe COVID-19: a Case Control Study

Abstract: ObjectiveBacterial infections are known to complicate respiratory viral infections and are associated with adverse outcomes in COVID-19 patients. A case control study was conducted to determine risk factors for bacterial infections where cases were defined as moderate to severe/critical COVID-19 patients with bacterial infection and those without were included as controls. Logistic regression analysis was performed. ResultsOut of a total of 50 cases and 50 controls, greater proportion of cases had severe or c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…These findings are similar to the results of previous studies, suggesting the need for strategies to help clinicians judiciously prescribe antibiotics in patients with COVID-19. [1][2][3][4][5][8][9][10]20 Previous studies conducted in the United States have shown that concomitant community acquired bacterial infections in COVID-19 patients are low based on microbiological data within the first 48 hours of admission. 4,5 In our study, we found only slightly higher rates of microbiologically confirmed infections than in other US studies, despite the fact that we reported all microbiologic data throughout hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to the results of previous studies, suggesting the need for strategies to help clinicians judiciously prescribe antibiotics in patients with COVID-19. [1][2][3][4][5][8][9][10]20 Previous studies conducted in the United States have shown that concomitant community acquired bacterial infections in COVID-19 patients are low based on microbiological data within the first 48 hours of admission. 4,5 In our study, we found only slightly higher rates of microbiologically confirmed infections than in other US studies, despite the fact that we reported all microbiologic data throughout hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Despite bacterial co-infection being reported in 1-8% of patients, rates of antibiotic prescribing have ranged from 57-95% in hospitalized patients. [1][2][3][4][5][6][7][8][9][10][11] Additionally, there are reports of increased consumption of antibiotics during the COVID-19 pandemic. 6,7,12,13 Over-prescribing of antibiotics may increase the risk of adverse events, nosocomial infection, and antibiotic resistance resulting in multidrug resistant bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the patients who died were infected with Gram-negative bacteria such as Acinetobacter sp. and P. aeruginosa (Nasir et al, 2021).…”
Section: Berkala Penelitian Hayati |mentioning
confidence: 97%
“…Each year, the number of patients infected with antibiotic-resistant bacteria grows, leading to the death of patients caused by resistant bacterial infections (Michael et al, 2014;Thongkrachang et al, 2016). Bacterial co-infections are commonly identified in viral respiratory infections and lead to the severe disease and mortality, as seen in influenza and H1N1 outbreak in 1918 and 2009, respectively (Feldman & Anderson, 2021;Nasir et al, 2021;Rice et al, 2012;Taubenberger & Morens, 2020). In addition, these infections able to suppress the host's immune system, raise antibiotics treatment sensitivity, and worsen the disease severity (Xin- Xu & Xiao-Nong, 2013).…”
Section: Bacterial Infections In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation